(untitled) (International relations and international law Journal, 2016)
This article analyzes the complex modern problems of nuclear non-proliferation in Central Asia . Copyright considering and analyzing the opinions of domestic and foreign experts on nuclear non-proliferation , offers his point of view . Also revealed the possibility of using the experience of Kazakhstan in the formation of the system of control over nuclear and other radioactive materials for the Central Asian countries to find solutions to similar problems . In this regard, the Central Asian countries in the context of integration processes have begun to form a unified system of control of nuclear and other radioactive materials that meets their equally the interests of other states supporting the nuclear nonproliferation regime.